Pengaruh Latihan Stength Endurance Terhadap Kemampuan Mawashi Geri Dalam Cabang Olahraga Karate Pada Atlet Dojo UKC - Tuanubun, Maria M.; Fenanlampir, Albertus; Solissa, Jonas (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study was to determine how much influence strength endurance has on the ability of Mawashi Geri in Karate for UKC Dojo Athletes. This research is a field experimental research with one group pre-test and post-test design. The population of this study amounted to 20 Karate athletes of UKC dojo athletes. Looking at the limited population and easy to reach, the research was conducted on the population. This research instrument uses (table of research aids for strength endurance training in the form of squat jump, heel rise, and step up and mawashi geri kick ability tests. The results of this study indicate that there is a significant positive effect as evidenced by the t_0 value of 4.85 with a significance level of 0.05 and 0.01. This means that there is a strong or high influence of strength endurance training on the ability of Mawashi geri in Karate martial arts UKC dojo athletes